2019
DOI: 10.1001/jamadermatol.2018.4556
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dipeptidyl Peptidase 4 Inhibitor Use With Risk of Bullous Pemphigoid in Patients With Diabetes

Abstract: IMPORTANCE Recent studies suggest that dipeptidyl peptidase 4 (DPP-4) inhibitors are associated with an increased risk of developing bullous pemphigoid (BP). Population-based studies on the association between DPP-4 inhibitors and BP are limited. OBJECTIVE To characterize the potential association between the use of DPP-4 inhibitors and an increased risk of developing BP. DESIGN, SETTING, AND PARTICIPANTS This retrospective, nationwide, population-based, case-control study using Korean insurance claims data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
102
2
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(129 citation statements)
references
References 33 publications
12
102
2
5
Order By: Relevance
“…The study also reported a strong association between vildagliptin and BP (OR, 5.08; 95% CI, 1.70–15.19; P = 0.004), followed by linagliptin (OR, 2.87; 95% CI, 1.06–7.79; P = 0.04), but not in sitagliptin (OR, 1.29; 95% CI, 0.79–2.08; P = 0.31). In Asia, a Korean retrospective, nationwide, case–control study of 670 case patients (DM and BP) and 670 control patients (DM only) showed that DPP‐4 inhibitors are associated with a significant risk of BP (adjusted odds ratio [aOR], 1.58; 95% CI, 1.25–2.00; P < 0.001) . The study further demonstrated that among all DPP‐4 inhibitors, vildagliptin was the most high risk of developing BP (aOR, 1.81; 95% CI, 1.31–2.50; P < 0.001).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The study also reported a strong association between vildagliptin and BP (OR, 5.08; 95% CI, 1.70–15.19; P = 0.004), followed by linagliptin (OR, 2.87; 95% CI, 1.06–7.79; P = 0.04), but not in sitagliptin (OR, 1.29; 95% CI, 0.79–2.08; P = 0.31). In Asia, a Korean retrospective, nationwide, case–control study of 670 case patients (DM and BP) and 670 control patients (DM only) showed that DPP‐4 inhibitors are associated with a significant risk of BP (adjusted odds ratio [aOR], 1.58; 95% CI, 1.25–2.00; P < 0.001) . The study further demonstrated that among all DPP‐4 inhibitors, vildagliptin was the most high risk of developing BP (aOR, 1.81; 95% CI, 1.31–2.50; P < 0.001).…”
Section: Discussionmentioning
confidence: 91%
“…The results of this large population‐based cohort study revealed that the use of DPP‐4 inhibitors was significantly related to an increased risk of BP with an aHR of 2.382 ( P = 0.017). The previous studies have elucidated the association between DPP‐4 inhibitors and BP . In 2019, a large population‐based cohort study of 8569 DPP‐4 inhibitor users and 160 205 non‐DPP‐4 inhibitor users was published by using the UK Clinical Practice Research Datalink .…”
Section: Discussionmentioning
confidence: 99%
“…Lee and colleagues performed a retrospective, nationwide case–control study using Korean insurance claims data from 2012 to 2016. Control cases with diabetes were randomly obtained from the same database after matching for age, gender and year of diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…There is little evidence that diabetes itself is involved in the development of Th2‐dominant PCM. However, antidiabetic agents, such a dipeptidyl peptidase‐4 inhibitor, increase the risk of development of bullous pemphigoid, a well‐known Th2‐dominant inflammatory skin condition . These observations therefore suggest the possibility of an association between PCM and diabetes.…”
Section: Discussionmentioning
confidence: 99%